Global catastrophic risks - Bostrom, Nick; Cirkovic, Milan M. (Oxford University Press, 2008)
In Global Catastrophic Risks 25 leading experts look at the gravest risks facing humanity in the 21st century, including natural catastrophes, nuclear war, terrorism, global warming, biological weapons, totalitarianism, advanced nanotechnology, general artificial intelligence, and social collapse. He developed the first mathematically explicit theory of observation selection effects and is the author of a number of seminal studies on the implications of future technologies.